2020
DOI: 10.1080/13683500.2020.1829570
|View full text |Cite
|
Sign up to set email alerts
|

Impact of health risk perception on avoidance of international travel in the wake of a pandemic

Abstract: As tourists are increasingly putting off their air travel due to the COVID-19 pandemic that has tremendously affected the travel and tourism industry, this study examined the role of negative affect, perceived health risk, perceived uncertainty, and mental wellbeing in forming travel attitudes and temporal avoidance behaviour to global destinations seriously-hit by the COVID-19 pandemic from a U.S. tourist perspective. The crosssectional online survey showed that negative affect as a result of COVID-19 signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
178
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(192 citation statements)
references
References 62 publications
8
178
1
5
Order By: Relevance
“…Second, based on the market segment of travel frequency, the three groups of high, medium, and low show substantial differences with respect to biosecurity behavior practices, significantly expanding past literature on the differences of travel frequencies and diseases spreading during outbreaks [ 1 , 2 , 6 , 7 , 14 , 15 , 34 ]. Third, biosecurity behavior practices are also significantly affected by attitude, followed by personal norm and social norm, expanding the literature between attitude toward international travel and behavior [ 16 ], between social norm and behavior for sustainability consumerism [ 45 ], and social norms and sustainable behavior [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, based on the market segment of travel frequency, the three groups of high, medium, and low show substantial differences with respect to biosecurity behavior practices, significantly expanding past literature on the differences of travel frequencies and diseases spreading during outbreaks [ 1 , 2 , 6 , 7 , 14 , 15 , 34 ]. Third, biosecurity behavior practices are also significantly affected by attitude, followed by personal norm and social norm, expanding the literature between attitude toward international travel and behavior [ 16 ], between social norm and behavior for sustainability consumerism [ 45 ], and social norms and sustainable behavior [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individual attitudes toward COVID-19 restriction measures lead to behaviors such as wearing face masks [ 22 ]. During the COVID-19 pandemic, attitude towards international travel has a significant effect on short- and long-term avoidance behavior [ 16 ]. In line with the literature review above, we suggest the following hypothesis:…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…HK protest is categorized as travel health risks because HK protest has threatened the safety of tourists exposure to blood, injury, and violence (WHO, 2012), and endangered travellers and local communities. Because of these known risks, which most tourists learned from media, tourists might form negative well-being travel attitudes and avoidance to HK temporarily (Chua et al, 2020; Yang et al, 2018). This has in turn induced a low trust level on revisit intention.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Under this theme, on the one hand, many scholars have conducted surveys on tourists' current reactions to travel under COVID-19 and found that the negative impact of COVID-19 has significantly affected the health risks perceived by tourists (for example, [25,[28][29][30]). As a result, tourists' avoidance of travel during the health crisis is caused.…”
Section: Tourist Perception and Decision-makingmentioning
confidence: 99%